Documenting the re-transformations of the built environment in Chingalire village, Malawi, for a sustainable development and resilience strategy: Practice contribution - Laura Natalia Chocontá Villamizar (Transformationsprozesse in Stadt und Land: Erkenntnisse, Strategien und Zukunftsperspektiven, 2024)
The village of Chingalire, Malawi, is being transformed into a model of sustainability. For the formulation of a development strategy, information on the village's changes was gathered over a year, focusing on the built environment since its beginnings in 1976. This research aims to initiate the documentation of these changes while reflecting on the quality, sustainability, and resilience of the village's built environment. It also provides an outlook for the development strategy, based on the acquired knowledge. Through semi-structured interviews with experts and villagers, the results show that most buildings were constructed by local builders (with no qualifications and a series of malpractices), with unsustainable materials, and following a 'modern' imaginary that negatively impacts the environment and is unaffordable for the locals. The lessons learned from previous constructions in Chingalire point towards preserving vernacular architectural values and appealing to new spatial designs. – – Chingalire, Malawi, wird derzeit in ein Modell der Nachhaltigkeit umgewandelt. Für die Formulierung seiner Entwicklungsstrategie wurden ein Jahr lang Informationen über die Veränderungen des Dorfes gesammelt, wobei der Schwerpunkt auf der bebauten Umwelt seit seinen Anfängen im Jahr 1976 lag. Ziel dieser Untersuchung ist es, diese Veränderungen zu dokumentieren und gleichzeitig über die Qualität, Nachhaltigkeit und Widerstandsfähigkeit der baulichen Umwelt des Dorfes nachzudenken und auf der Grundlage der gewonnenen Erkenntnisse einen Ausblick auf die Entwicklungsstrategie zu geben. Anhand halbstrukturierter Interviews mit Experten und Dorfbewohnern zeigen die Ergebnisse, dass die meisten Gebäude von lokalen Bauunternehmern (ohne Qualifikation und mit einer Reihe von Missständen) errichtet wurden, die nicht-nachhaltige Materialien verwendeten und einer "modernen" Vorstellung folgten, die sich negativ auf die Umwelt auswirkt und für die Einheimischen unerschwinglich ist. Die Lehren, die man aus früheren Bauten in Chingalire gezogen hat, weisen darauf hin, dass man die Werte der einheimischen Architektur bewahren und neue Raumkonzepte ansprechen sollte.
urn:nbn:de:0156-1171140; hdl:10419/285312; https://econpapers.repec.org/RePEc:zbw:arlfob:285312
Keywords: 710; Strategic rural sustainable development; Rural resilience; Sustainable architectural design; International cooperation; Strategische nachhaltige Entwicklung des ländlichen Raums; ländliche Resilienz; nachhaltige architektonische Gestaltung; internationale Zusammenarbeit